2010
DOI: 10.4103/0250-474x.84582
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite-alginate composites as a drug delivery system: Intercalation and In vitro release of diclofenac sodium

Abstract: Diclofenac sodium and alginate was intercalated into montmorillonite to form uniform sized beads by gelation method. The structure and surface morphology of the synthesized composite beads were characterized by powdered X-ray diffraction, Fourier transform infrared spectroscopy, thermo gravimetric analysis and scanning electron microscopy. Diclofenac release kinetics of the composite in simulated intestinal fluid medium (pH 7.4) and effect of montmorillonite content on the in vitro release of diclofenac from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Therefore, in the fingerprint region, the band at 1645 cm −1 corresponding to the group stretching vibrations of the newly formed imine bonds between chitosan and citral appeared in the spectra of the drug delivery systems, while the vibration of the aldehyde unit of cytral (1675 cm −1 ) disappeared, indicating that the imination process was not impeded by the presence of DCF ( Figure 1 ). Upon a deeper view, it could be observed that the band at 1725 cm −1 , which is characteristic of the stretching vibrations of the C=O groups in the IR spectrum of the DCF drug, also appeared in the spectra of the drug delivery systems as a shoulder, which was a sign of DCF’s presence in the matrix [ 26 , 27 ]. Moreover, this band was a little bit shifted in the spectra of the drug delivery systems, very probably due to the strong interactions with the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in the fingerprint region, the band at 1645 cm −1 corresponding to the group stretching vibrations of the newly formed imine bonds between chitosan and citral appeared in the spectra of the drug delivery systems, while the vibration of the aldehyde unit of cytral (1675 cm −1 ) disappeared, indicating that the imination process was not impeded by the presence of DCF ( Figure 1 ). Upon a deeper view, it could be observed that the band at 1725 cm −1 , which is characteristic of the stretching vibrations of the C=O groups in the IR spectrum of the DCF drug, also appeared in the spectra of the drug delivery systems as a shoulder, which was a sign of DCF’s presence in the matrix [ 26 , 27 ]. Moreover, this band was a little bit shifted in the spectra of the drug delivery systems, very probably due to the strong interactions with the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The vibrational band at about 1734 cm −1 corresponds to C=O stretching of PVA and SA [21] [22]. The band at about 836 cm −1 is attributed to AlMgOH bending vibrations [23]. In the case of MMT filled PVA/SA, FR-IR spectra shows shifts in some bands (1423 cm −1 , 1243 cm −1 and 1086 cm −1 ) which is essentially due to Si-O stretching: out of plane and in-plane which is absent in pure films.…”
Section: Ft-ir Studiesmentioning
confidence: 97%
“…Montmorillonite layers and sheets in bentonite make it a suitable nanoclay for drug delivery [28,29]. Its use in sustained and targeted drug release for targeted chemotherapy has also been investigated [30][31][32].…”
Section: Bentonitementioning
confidence: 99%